Are all blood-based postal sampling kits the same? A comparative service evaluation of the performance of dried blood spot and mini tube sample collection systems for postal HIV and syphilis testing. Issue 3 (19th November 2020) - Page, Matthew; Atabani, Sowsan; Arumainayagam, Joseph; Wilson, Steven; Hartland, Daniel; Taylor, Stephen
Abstract : Objectives: We comparatively evaluated two HIV and syphilis blood sampling kits (dried blood spot (DBS) and mini tube (MT)) as part of an online STI postal sampling service that included tests for chlamydia and gonorrhoea. We aimed to see how the blood collection systems compared regarding sample return rates and result rates. Additionally, we aimed to observe differences in false-positive results and describe a request-to-result ratio (RRR)—the required number of kit requests needed to obtain one successful result. Methods: We reviewed data from an online postal STI kit requesting service for a client transitioning from MT to DBS blood collection systems. We described service user baseline characteristics and compared kit requests, kit and blood sample return rates, and the successful resulting rates for HIV and syphilis for MT and DBS. Pearson's χ 2 and Fisher's exact test were used to determine statistical differences, and statistical formulae were applied to produce CIs for differences in proportions. Results: 5670 STI postal kit requests from a Midlands region were reviewed from 6 September 2016–2 January 2019 (1515 MT and 4155 DBS). Baseline characteristics between the two groups were comparable (68.0% female, 74.0% white British and 87.5% heterosexual, median age 26 years). Successful processing rates for DBS were 94.6% and 54.4% for MT (p<0.001) with a percentage difference of 40.2% (95% CI 36.9% to 43.4%). The RRR for MT was 2.9 cf. 1.6 for DBS. False-positive results for MT samples were 5.2% (HIV) and 0.4% (syphilis), and those for DBS were 0.4% (HIV) and 0.0% (syphilis). Conclusions: This comparative analysis demonstrated the superior successful processing rates for postal DBS collection systems compared with MT. Reasons for this included insufficient volumes, high false-positive rates and degradation of blood quality in MT samples. A postal sampling service using DBS to screen for HIV, syphilis and other blood-borne viruses could be a viable alternative.